SISTEM PENGENDALIAN SUHU PADA GREENHOUSE UNTUK BUDIDAYA TANAMAN PAPRIKA MENGGUNAKAN LOGIKA FUZZY METODE MAMDANI - Hayyan, Muhammad Rafif; Nusantoro, Goegoes Dwi; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2023)
The paprika plant (Capsicum annuum L.) is a plant native to South America that requires sub-tropical climate conditions togrow. In Indonesia, paprika grows well in the highlands at an altitude of 1000 - 1,500 m above sea level, requiring an idealtemperature of between 21ºC - 27ºC during the day and 13ºC - 18ºC at night. Extreme temperatures above 38ºC during theday and 32ºC at night can be detrimental to the growth of paprikas. To overcome the problem of temperature control in paprikaplants in Indonesia, the author designed a smart greenhouse with a temperature control system based on fuzzy logic. Fuzzylogic was chosen because of its flexibility in making decisions. This smart greenhouse uses cooling and heating actuators tomaintain the temperature inside. This research involved several stages of testing, including placement testing, actuator testing,and overall system testing. Placement tests showed temperature differences between various sides of the smart greenhouse, soit was necessary to use an actuator to even out the temperature inside. Testing the actuator explained that the cooling actuatorcontained a blower fan which functioned to even out the temperature inside the smart greenhouse and a peltier fan functionedto lower the temperature inside the smart greenhouse. Apart from that, there is a heating actuator in the form of a heater whichfunctions to increase the temperature inside the smart greenhouse. After collecting data from this test, proceed with testing theentire system. In this test, there are two conditions tested: day conditions with a setpoint of 24ºC and night conditions with asetpoint of 15ºC. Day conditions reach a steady state error of 1.26%, while night conditions do not reach a steady state errorbecause the cooling actuator is unable to approach the desired setpoint. The test results show that the system can maintain thetemperature inside the smart greenhouse. In addition, tests were carried out on paprika plants inside and outside the smartgreenhouse. The results showed that paprika plants grown in the smart greenhouse produced better development compared tothose planted outside. This research shows that a temperature control system based on fuzzy logic in a smart greenhouse canincrease the growth of paprika plants. Keywords: Paprika Plants, Fuzzy Logic, Smart Greenhouse, Temperature